Strategic Implementation of Multipurpose Financing in Islamic Banking - Khairisma; Muhammad Yoesoef, Yoesrizal; Putri Mellita Sari, Cut; Nailufar, Fanny; Andyna, Cut (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2025)
This study explores the strategic implementation of multipurpose financing at Bank Aceh Syariah Bireuen Branch using a qualitative descriptive approach with a SWOT analytical framework. Six informants were involved, consisting of three bank staff and three customers selected purposively based on their relevance to the financing process. Data were collected through interviews, observations, documents, and questionnaires, then analyzed using IFAS–EFAS matrices to identify internal and external strategic factors. The results show that the branch is positioned in SWOT Quadrant II, indicating strong internal capabilities amidst significant external threats. Key strengths include sharia-compliant financing, responsive service, and wide community trust, while the main challenges stem from limited product variety, modest promotion, and rising competition from national Islamic banks with advanced digital platforms. Based on the SWOT positioning, the study recommends prioritizing feasible strategies such as product diversification, digital development, and customer-centered outreach. This study contributes to the discourse on Islamic regional banking by offering a contextualized, branch-level analysis of strategy formulation. Future research is encouraged to involve more branches and diverse stakeholders to expand the applicability of findings.